2001
DOI: 10.1042/cs1020051
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of mechanical arterial properties: clinical, experimental and therapeutic aspects

Abstract: Ageing and disease states associated with an increase in cardiovascular events alter the physical characteristics of blood vessel walls and impair the pulsatile function of arteries. An accumulating body of evidence indicates that impaired pulsatile function of arteries provides important prognostic and therapeutic information beyond that provided by traditional blood pressure measurements. A variety of techniques are currently employed to evaluate the mechanical properties of arteries. All techniques have the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
52
0
5

Year Published

2003
2003
2010
2010

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 89 publications
(59 citation statements)
references
References 193 publications
(209 reference statements)
2
52
0
5
Order By: Relevance
“…This finding agrees with the statement that the increase in systolic pressure of large arteries with age is greater than that in small arteries (O'Rourke 1990, Li 2000. Furthermore, the general statement of systolic pressure increase in older subjects, in part, is attributed to age-related systemic increases in resistance and a reduction in compliance (McVeigh et al 2002;Berger and Li 1990) in accord with changes found in this work (Fig. 11).…”
Section: Discussionsupporting
confidence: 82%
“…This finding agrees with the statement that the increase in systolic pressure of large arteries with age is greater than that in small arteries (O'Rourke 1990, Li 2000. Furthermore, the general statement of systolic pressure increase in older subjects, in part, is attributed to age-related systemic increases in resistance and a reduction in compliance (McVeigh et al 2002;Berger and Li 1990) in accord with changes found in this work (Fig. 11).…”
Section: Discussionsupporting
confidence: 82%
“…In addition, central arterial stiffness has been highlighted as an independent prognosticator of cardiovascular events in some populations (6,19 -21). A wide variety of methods have been proposed for the evaluation of aortic stiffness (22,23). Most of these techniques require knowledge of area and pressure, the latter obtained directly only by invasive means.…”
Section: Discussionmentioning
confidence: 99%
“…Further, the effect of angiotensin II may result in vascular wall structure changes (29). Endothelial dysfunction affects pulsatile pressure buffering and vasodilation of the arterial system through the elaboration of vasoactive substances, such as endothelial-derived relaxing factor (22,29). HCM patients also may have abnormal left ventricular baroreceptor stimulation, resulting in inappropriate vasodilation (30).…”
Section: Figurementioning
confidence: 97%
“…4,5 Z ART has proven to be a reliable and reproducible representation of after-load as it incorporates several key aspects of the arterial system, including resistance, compliance (⌬pressure Ϭ ⌬volume), blood inertia (accelerate blood at rest through vasculature) and reflected pulse pressure waves. 6 Z ART increases with LV dysfunction 7,8 and aging. 9,10 Increases in Z ART adversely impact myocardial load, resulting in increased wall stress and reduced stroke volume.…”
mentioning
confidence: 97%